(untitled) (Editora Impacto Científico, 2025)
Service quality and customer satisfaction are fundamental strategic elements for organizational competitiveness, especially in the healthcare sector, where patient care demands precision, empathy, and reliability. This study aimed to evaluate customer perception of the quality of care provided by a clinical analysis laboratory located in the municipality of Dourados-MS. To answer the research question—what is the degree of customer satisfaction with the service offered?—a descriptive case study was conducted. Methodological procedures employed included bibliographic research and the application of a structured questionnaire to service users. The results indicated that the quality of care directly influences customer loyalty, highlighting the importance of constant improvement practices, welcoming atmosphere, and efficiency. It is concluded that the laboratory presents satisfactory performance according to customer perception, although there are opportunities for improving its processes and strengthening its competitive advantage. DOI: https://doi.org/10.56238/edimpacto2025.090-057